أنماط النمو السكاني الحضري في المدن الليبية الكبرى: تحليل جغرافي بشري للفترة ما بعد 2011 (Comprehensive Journal of Science, 2025)
This study aims to analyze the transformations of urban population growth in major Libyan cities after 2011 from a human-geographic perspective. It focuses on the patterns of population distribution, spatial expansion trends, the driving factors behind these transformations, and their resulting urban, social, and infrastructural impacts. The study adopts a descriptive-analytical approach supported by statistical data, international reports, and spatial analysis of urban expansion in the country’s main cities.The findings indicate that post-2011 urban growth in Libya has been primarily driven by internal displacement resulting from conflict, alongside socio-economic shifts that encouraged migration from rural to urban areas. This growth has concentrated in cities such as Tripoli, Benghazi, and Misrata, which experienced unbalanced horizontal expansion and increasing pressure on infrastructure and services, with evident spatial disparities between central and peripheral areas.